Energy policy and land-use planning : an international perspective - Cope, David R.; Hills, Peter (Peter R.); James, Peter, 1953- (Urban and regional planning series, 1984)
This book fills a gap in the available literature on energy policy by dealing with the relationship between energy and land-use planning. It considers, in a systematic way, energy developments in national, regional and local planning policy contexts, concentrating particularly on energy supply issues in Europe.